Digitalisasi Layanan Sistem Informasi Pemasaran dan Laporan Persediaan Barang - Mufadhol (UNIVERSITAS STEKOM, 2020)
Abstract Companies require a management information sistem that is good to making work efficiency and effectiveness and for improve service to customers. The increasing competition will force companies that are growing and that has been developed to provide effective and efficient services, so that the goals and objectives can be achieved by proper and eventually the company can compete in maintaining business continuity. Technological advancements encourage every type of business to keep abreast of developments and continue to improve their ability to manage data and information needed. This paper will discuss how to design, develop and implementation services as well as analyzing digital information sistem fatherly sales and inventory reports. With this method of digitizing sistems through information sistem service is possible to awaken a reliable information sistem, so that data can be stored with appropriate and practical, the information needed can be searched quickly and accurately as well as the necessary reports can be viewed in an easy and detailed.